(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article describes the issue of formation of indicators for the assessment of the quality of Latin language teaching to students of medical higher educational institutions, in particular, the analysis of the issue of indicators and criteria for evaluating the process of Latin language teaching.